Lift Off Process on Fabrication of Carbon Monoxide (CO) Gas Sensor Devices - Slamet Widodo; Goib Wiranto (ALCHEMY Jurnal Penelitian Kimia, 2014)
This paper  discuss  the design and fabrication of microdevice to be used  as platform for  CO (Carbon monoxide)  gas sensor based on tin dioxide (SnO2). The device has been designed on silicon substrate with an active area of 3x3 mm2, and  it is consist of  bonding pad, heater, electrode, and temperature sensor components. The minimum feature size  used is 50 microns, as allowed by the capability of photolithographic process. The formation of microdevice structure  was carried out by  lift-off  technique on platinum (Pt) layer, which was deposited by DC sputtering with aluminum (Al) as sacrificial layer. The overall chip dimension is 5x5 mm2. The measurement  that was  conducted to study the  characteristic of resistance  asfunction  of  temperature  has  shown   that  the  heater  and  temperature  sensor elements  could  work  as  expected,  in  which  their  resistances  change  linearly  as  the temperature of the substrate increase by  20–200  °C. The  resistance values of the heater increase  500–1000  ohm.  Meanwhile,  the  resistance  increasing  for  temperatur  sensor  is between  100–300 ohm.